1990
DOI: 10.3109/00016489009122527
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sinus Empyema in Adults: A Coordinated Nordic Multicenter Trial of Cefixime vs. Cefaclor

Abstract: In sinus empyema, H. influenzae is the most prevalent pathogen in some subpopulations and in case of therapeutic failure. Cefixime, the first oral cephalosporin of the 3rd generation, is highly potent in vitro against H. influenzae. To study the efficacy and safety of cefixime in adults with acute sinusitis, a coordinated, double-blind multicenter trial was designed for purulent cases, as confirmed by antral aspiration. A total of 364 patients were enrolled in the study with 125 cases randomized to the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…These and a variety of other gram-positive and gram-negative pathogens, including anaerobes all frequently associated with acute bacterial sinusitis, were also isolated [17]. Nonetheless, no statistical differences were found in the number of isolates in our three treatment groups, although there were slightly more H. influenzae isolates than reported in other studies [1,3,14].…”
Section: Discussioncontrasting
confidence: 64%
“…These and a variety of other gram-positive and gram-negative pathogens, including anaerobes all frequently associated with acute bacterial sinusitis, were also isolated [17]. Nonetheless, no statistical differences were found in the number of isolates in our three treatment groups, although there were slightly more H. influenzae isolates than reported in other studies [1,3,14].…”
Section: Discussioncontrasting
confidence: 64%
“…Of note, the four studies that did not require either radiographic evidence or purulence had the highest bacterial prevalence on culture (61.1%). These studies were from 1976, 1979, and 1990, and are four of the seven oldest studies in our meta‐analyses, but no other common characteristics seem to make the patients in these studies more likely to have bacterial ARS compared to patients in later studies.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of optimal dosing in the treatment of community-acquired bacterial sinusitis is emphasized in a review of several antibiotic trials in which cultures of sinus aspirates obtained before and after treatment were used to evaluate microbiological efficacy [8]. In this review, 2 studies showed that the bacteriologic cure rate was 90% in patients whose antibiotic concentration was greater than the MIC for the pathogen after treatment but only 45% in patients whose antibiotic concentration was less than the MIC for the organism (table 4) [8,11,12,37,38]. It also showed that in several other similarly designed studies, the bacteriologic cure rate was 93% in patients who received an appropriate dose of an appropriate drug but only 71% in those who received a suboptimal dose [8].…”
Section: Management Of Sinusitis: a Continuing Challengementioning
confidence: 96%